A case of Ross syndrome presented with Horner and chronic cough - Baran, Aslihan; Balbaba, Mehmet; Demir, Caner F.; Ozdemir, Hasan H. (Medknow Publications & Media Pvt Ltd, 2014)
Ross syndrome is a rare sweating disorder associated with Adie's tonic pupil, decreased or diminished tendon reflex and unknown etiology. Although autonomic disturbances affecting sudomotor and vasomotor functions are seen commonly, they are rarely symptomatic. While Ross syndrome is typically characterized with dilated tonic pupil, it may be rarely manifested with miotic pupils (little old Adie's pupil), which can make diagnosis difficult. In this article, we aim to specify the atypical clinical manifestations of syndrome by means of Ross syndrome manifested by autonomic symptoms, Horner syndrome, chronic cough together with bilateral little old Adie's pupil.
Keywords: Chronic cough; hemihyperhidrosis; Horner syndrome; little old adie's pupil